RNA-Seq for the detection of differential expressed genes under several experimental conditions - Fernandes, Isabel Cristina Moniz (2021)
Tese de mestrado, Bioinformática e Biologia Computacional, 2021, Universidade de Lisboa, Faculdade de Ciências